Monte Carlo Simulation on TiO2 : Water Thickness Determination and Electron Scattering Study on Wet Material - Rahmat Firman Septiyanto; Isriyanti Affifah (Universitas Sultan Ageng Tirtayasa, 2021)
Analysis of the three-dimensional (3D) structure of a material is indispensable in various fields of science, especially in materials science. Several studies have been conducted to observe the 3D structure of wet samples in a water-soluble environment using ESEM (Environmental Scanning Electron Microscopy) with tomography. The principle of tomography is based on the acquisition of a series of image projections at different angles of inclination and the calculation of the volume of the 3D reconstruction with a special algorithm. In this study, Monte Carlo simulation was used to analyze the optimum water thickness that could be detected in TiO2 wet material and the number of electron scattering captured to calculate the interaction volume dimensions. The results showed that the optimum thickness was achieved at 400 nm for the thickness of the wet sample and 10 nm for the thickness of the water.